Appendiceal mucinous neoplasm with myxoglobulosis occurring 3 years after perforated barium appendicitis: a case report - Fujii, Takatsugu (Surg Case Rep, 2019)
BACKGROUND: Myxoglobulosis is considered a subtype of appendiceal mucinous neoplasm (AMN). Factors affecting the occurrence of myxoglobulosis include proximal appendiceal obstruction and mucosal secretion at the residual appendiceal mucosa. In addition, myxoglobulosis has also been reportedly associated with persistent chronic inflammation. We report a case of AMN with myxoglobulosis occurring 3 years after perforated barium appendicitis and the importance of caution during surgery for barium peritonitis and elucidate the pathology of myxoglobulosis. CASE PRESENTATION: A 45-year-old man with an AMN underwent laparoscopic ileocecal resection 3 years after peritonitis caused by perforated barium appendicitis. The patient had a medical history of perforated barium appendicitis after barium swallow imaging, which was treated conservatively 3 years ago. Computed tomography (CT) revealed cystic enlargement of the appendix and remnant barium around the appendix. He was then pathologically diagnosed with a low-grade AMN based on the resected specimen, and the appendix filled with white globules was diagnosed as myxoglobulosis. When barium is not absorbed, it causes chronic inflammation. As barium was observed around the appendix, prolonged inflammation, and appendicitis may have contributed to the myxoglobulosis. The circumference of the appendix firmly adhered to the surrounding tissue with barium; hence, it was difficult to perform appendectomy. Barium that enters the anastomotic site causes stenosis of this part; therefore, excision of the ileocecal region in the intestinal part where barium is not present was selected instead of appendectomy. Colonoscopy performed 1 year after surgery and showed no evidence of anastomotic stricture. CONCLUSION: This case suggested that barium peritonitis caused strong adhesions with the surrounding tissue; thus, careful manipulation was necessary to avoid perforating the appendix. Appendectomy and partial cecal resection were predicted to be difficult because of adhesion by barium. In addition, the ileocecal resection was selected because we had to choose an anastomotic site without barium. The perforated appendicitis caused stenosis of the appendix orifice, and barium surrounding the appendix caused persistent chronic inflammation. This was suggested to contribute to the myxoglobulosis.